Discussion: Food - Reconstruction and the Public (EXARC, 2013)
For a BBC program in 1954, Sir Mortimer Wheeler tasted a reconstruction of the Tollund Man’s last supper, which turned out to be a tasteless mush. This led him to announce: "I believe that the poor chap of Tollund committed suicide because he could stand his wife's cooking no longer!" While archaeology-inspired cookery is an important and attractive way of involving the public, it also has some drawbacks. How authentic can we be? What about health and safety? Should we only cook what the public will like?